2020
DOI: 10.4236/msa.2020.117033
|View full text |Cite
|
Sign up to set email alerts
|

Co-Doped Rare-Earth (La, Pr) and Co-Al Substituted M-Type Strontium Hexaferrite: Structural, Magnetic, and Mossbauer Spectroscopy Study

Abstract: The present study investigates the influence of La 3+ and Pr 3+ doping on the structural, magnetic properties, and hyperfine fields of Sr 0.7 RE 0.3 Fe 12−2x Co x-Al x O 19 , (RE: La 3+ and Pr 3+ , x = 0.0-0.8) hexaferrite compounds prepared via auto-combustion technique. The XRD analysis shows a linear decrease in a and c lattice and unit cell volume contraction with the content x. The room temperature magnetic study shows that for the Pr 3+ doped Sr 0.7 Pr 0.3 Fe 12−2x Co x Al x O 19 (Pr 3+-SrM), the magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…It is observed that there is a significant fall in Hc from 4.20kOe at Al content (x) = 0 to Hc = 3.13 kOe and Hc = 2.85kOe for BAl-2 and BAl-4 samples, respectively. The coercivity decreased with the increase in Al 3+ content due to decrease in magneto-crystalline anisotropy [3,8,10,13]. Our results on the magnetic properties of Al 3+ substituted BaFe(12-x)AlxO19 M-type ferrite for x = 2.0, and x = 4.0 are in good agreement with those already reported for the substituted barium hexaferrite (Al, Cr) [15].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It is observed that there is a significant fall in Hc from 4.20kOe at Al content (x) = 0 to Hc = 3.13 kOe and Hc = 2.85kOe for BAl-2 and BAl-4 samples, respectively. The coercivity decreased with the increase in Al 3+ content due to decrease in magneto-crystalline anisotropy [3,8,10,13]. Our results on the magnetic properties of Al 3+ substituted BaFe(12-x)AlxO19 M-type ferrite for x = 2.0, and x = 4.0 are in good agreement with those already reported for the substituted barium hexaferrite (Al, Cr) [15].…”
Section: Resultssupporting
confidence: 91%
“…Consequently, a decrease in Hc with an increase in Al 3+ content is expected behavior for a magnetic microwave absorber application. The reflection loss of electromagnetic wave (for the case of a metal-backed single layer) can be calculated through the mathematical equation approach as follows: …………..... (2) with Zin given by = …..………… (3) where r and r are the complex magnetic permeability and electric permittivity of the medium, c is the velocity of light in free space, f is the frequency and d is the absorber thickness [1,8]. The variation in reflection loss (RL) with frequency for all samples of 2.0 mm thickness in the frequency range of 9.0-13 GHz is shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[215] Efforts have been made to enhance the magnetic characteristics of hexaferrite by cationic substitution to meet a variety of applications. [148,216] These includes efforts on altering the intrinsic properties of hexaferrites by replacing with either single or multiple trivalent metal ions such as La 3+ , [217][218][219][220][221] Tb 3+ , [222,223] Nd 3+ , [138][139][140][224][225][226] Eu 3+ , [227] Dy 3+ , [228,229] Sm 3+ , [230,231] Cr 3+ , [232,233] Al 3+ , [185,186,234,235] Gd 3+ , [236][237][238] Sc 3+ , [239] Er 3+ , [240][241][242] Pr 3+ , [243] Yb 3+ , [244] Ce 3+ , [245] La 3+ -Pr 3+ , [246] La 3+ -Nd 3+ , [247] Nd 3+ -Sm 3+ , [248] Nb 3+ -Y 3+ , [249] La 3+ -Ce 3+ , [250] Er 3+ -Cr 3+ , [251] Dy 3+ -Nd 3+ -Pr 3+ [252] or a suitable mix of divalent and trivalent ions such as Tb 3+ -Mn 2+ , …”
Section: Properties Of Hexagonal Ferritesmentioning
confidence: 99%
“…These improvements can be achieved by doping with rare earth trivalent cations, for example, Nd 3+ [15][16][17][18]. La 3+ [19,20], Pr 3+ [21,22], and Gd 3+ [23]. These elements are the most studied and therefore have had the greatest impact on various investigations although there are more possibilities of rare earth for doping such as Sm 3+ , Er 3+ , Yb 3+ , Eu 3+ , and Dy 3+ [24,25].…”
Section: Introductionmentioning
confidence: 99%